Hydrometeorology organizes intra‐annual patterns of tree growth across time, space and species in a montane watershed. Issue 4 (27th June 2017) - Martin, Justin; Looker, Nathaniel; Hoylman, Zachary; Jencso, Kelsey; Hu, Jia
Summary: Tree radial growth is often systematically limited by water availability, as is evident in tree ring records. However, the physiological nature of observed tree growth limitation is often uncertain outside of the laboratory. To further explore the physiology of water limitation, we observed intra‐annual growth rates of four conifer species using point dendrometers and microcores, and coupled these data to observations of water potential, soil moisture, and vapor pressure deficit over 2 yr in the Northern Rocky Mountains, USA. The onset of growth limitation in four species was well explained by a critical balance between soil moisture supply and atmospheric demand representing relatively mesic conditions, despite the timing of this threshold response varying by up to 2 months across topographic and elevation gradients, growing locations, and study years. Our findings suggest that critical water deficits impeding tissue growth occurred at relatively high water potential values, often occurring when hydrometeorological conditions were relatively wet during the growing season (e.g. in early spring in some cases). This suggests that species‐specific differences in water use strategies may not necessarily affect tree growth, and that tissue growth may be more directly linked to environmental moisture conditions than might otherwise be expected.